Perinatal exposure to PFOS and sustained high-fat diet promote neurodevelopmental disorders via genomic reprogramming of pathways associated with neuromotor development - Issam Hmila (9239059) (2024)
Perfluorooctanesulfonic acid (PFOS) is a neurotoxic widespread organic contaminant which affects several brain functions including memory, motor coordination and social activity. PFOS has the ability to traverse the placenta and the blood brain barrier (BBB) and cause weight gain in female mice. It’s also known that obesity and consumption of a high fat diet have negative effects on the brain, impairs cognition and increases the risk for the development of dementia. The combination effect of developmental exposure to PFOS and the intake of a high-fat diet (HFD) has not been explored. This study investigates the effect of PFOS and /or HFD on weight gain, behavior and transcriptomic and proteomic analysis of adult brain mice. We found that female mice exposed to PFOS alone showed an increase in weight, while HFD expectedly increased body weight. The combination of HFD and PFOS exacerbated generalized behavior such as time spent in the center and rearing, while PFOS alone impacted the distance travelled. These results suggest that PFOS exposure may promote hyperactivity. The combination of PFOS and HFD alter social behavior such as rearing and withdrawal. Although HFD interfered with memory retrieval, biomarkers of dementia did not change except for total Tau and phosphorylated Tau. Tau was impacted by either or both PFOS exposure and HFD. Consistent with behavioral observations, global cerebral transcriptomic analysis showed that PFOS exposure affects calcium signaling, MAPK pathways, ion transmembrane transport, and developmental processes. The combination of HFD with PFOS enhances the effect of PFOS in the brain and affects pathways related to ER stress, axon guidance and extension, and neural migration. Proteomic analysis showed that HFD enhances the impact of PFOS on inflammatory pathways, regulation of cell migration and proliferation, and MAPK signaling pathways. Overall, these data show that PFOS combined with HFD may reprogram the genome and modulate neuromotor development and may promote symptoms linked to attention deficit-hyperactivity disorders (ADHD) and autism spectrum disorders (ASD). Future work will be needed to confirm these connections. Other Information Published in: Ecotoxicology and Environmental Safety License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ecoenv.2024.116070